2012
DOI: 10.1159/000338464
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Agonist Exendin-4 Leads to Reduction of Weight and Caloric Intake in a Rat Model of Hypothalamic Obesity

Abstract: Background: Hypothalamic obesity caused by damage of medial hypothalamic nuclei presents a therapeutic challenge. Glucagon-like peptide-1 agonist exenatide (synthetic version of exendin-4 (Ex4)), used for treatment of diabetes, causes weight loss via hindbrain signaling. Methods: We tested Ex4 in an established rat model of medial hypothalamic lesions. Lesion and control animals were administered either daily intraperitoneal injections of 1 µg·kg–1 Ex4 or saline for 9 days. Results: In our rat model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 84 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…Intraperitoneal injection of GLP‐1RA liraglutide and exendin‐4 also reduced food intake in non‐diabetic rats. In addition, subcutaneous injections of liraglutide significantly reduced the food intake and bodyweight in diabetic ob / ob and db / db mice, as well as in obese candy‐fed rats, obese mini‐pigs and obese rats carrying hypothalamic lesions. It was also shown that GLP‐1 or GLP‐1RA liraglutide infusion reduced food intake and reduced gastric emptying in healthy volunteers, patients with type 1 diabetes and patients with type 2 diabetes.…”
Section: Diabetes‐related Comorbiditiesmentioning
confidence: 93%
“…Intraperitoneal injection of GLP‐1RA liraglutide and exendin‐4 also reduced food intake in non‐diabetic rats. In addition, subcutaneous injections of liraglutide significantly reduced the food intake and bodyweight in diabetic ob / ob and db / db mice, as well as in obese candy‐fed rats, obese mini‐pigs and obese rats carrying hypothalamic lesions. It was also shown that GLP‐1 or GLP‐1RA liraglutide infusion reduced food intake and reduced gastric emptying in healthy volunteers, patients with type 1 diabetes and patients with type 2 diabetes.…”
Section: Diabetes‐related Comorbiditiesmentioning
confidence: 93%
“…Recently, the CMHL rat model was used to test the efficacy of three pharmaceutical agents that act downstream of the mediobasal hypothalamus to reduce food intake and body weight. These agents include MTII, the glucagon-like peptide (GLP)-1 agonist exenatide and the psychomotor stimulant methylphenidate [ 139 , 140 ]. Both sham-lesioned and CMHL rats exhibited significant reductions in both food intake (lesion −20.8%, control −13.7%) and body weight when treated with exenatide relative to saline-controls [ 139 ].…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…These agents include MTII, the glucagon-like peptide (GLP)-1 agonist exenatide and the psychomotor stimulant methylphenidate [ 139 , 140 ]. Both sham-lesioned and CMHL rats exhibited significant reductions in both food intake (lesion −20.8%, control −13.7%) and body weight when treated with exenatide relative to saline-controls [ 139 ]. Using a crossover design study, treatment with methylphenidate in both sham and CHML rats caused a significant decrease in food intake (CMHL −23%, p = 0.008; control −20%, p = 0.002) and body weight compared to saline-treated controls [ 140 ].…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…The HO rats were treated with GLP1RA. Interestingly, a stronger reduction in food intake was found in rats who received exendin-4 compared to those who received saline injections in both lesioned rats and controls (difference between saline- and exendin-4-injected rats: lesion –20.8%, p = 0.001, control –13.6%, when adjusted for the effect of saline injection) [57], supporting this theory.…”
Section: Treatmentmentioning
confidence: 87%